Ralph Ellison’s ‘Bluesisms’: Expressionistic and Surrealistic Imagery in Invisible Man’s Blues Motifs - Alonso Recarte, Claudia (Estudios Ingleses de la Universidad Complutense, 2009)
Ralph Ellison’s epic novel, Invisible Man (1952), has often been analysed for its use of jazz and blues rhythms and motifs in the development of the leading character, speech intonations and narrative riffs. This article attempts to provide some insight into how Ellison relied on expressionistic and surrealistic imagery for the elaboration of these motifs in the novel’s Prologue. Stepping away from the critics’ frequent associations between Ellison’s narrative and the art of the blues painter Romare Bearden, this paper seeks to establish the influence he received from expressionists and surrealists for the evocation of the iconography and spaces in the novel. With an expressionistically-characterized Louis Armstrong as the point of departure, the Prologue spatially transcends into a dream world around which expressionistic forms and colors and surrealistic psychic automatism revolve. Through this experimental enterprise, Ellison not only sought to depict visuals consistent with the inner chaos of the character’s mind, but also to provide a model for black literature which, unrestricted by the social realism of the Negro protest novel of the 1940s, employed earlier revolutionary European aesthetics and the use of the mythical method for inspiration.